Autosomal recessive retinitis pigmentosa with RP1 mutations is associated with myopia. Issue 10 (16th April 2015) - Chassine, Thomas; Bocquet, Béatrice; Daien, Vincent; Avila-Fernandez, Almudena; Ayuso, Carmen; Collin, Rob WJ; Corton, Marta; Hejtmancik, J Fielding; van den Born, L Ingeborgh; Klevering, B Jeroen; Riazuddin, S Amer; Sendon, Nathacha; et al.
Abstract : Objective: To determine the refractive error in patients with autosomal recessive retinitis pigmentosa (arRP) caused by RP1 mutations and to compare it with that of other genetic subtypes of RP. Methods: Twenty-six individuals had arRP with RP1 mutations, 25 had autosomal dominant RP (adRP) with RP1 mutation, 8 and 33 had X-linked RP (xlRP) with RP2 and RPGR mutations, respectively, 198 and 93 had Usher syndrome and arRP without RP1 mutations, respectively. The median of the spherical equivalent (SE) and the IQR (Q25–Q75) was determined and multiple comparisons were performed. Results: arRP patients with RP1 mutations had SE median at −4.0 dioptres (D) OD (Ocula Dextra); −3.88 D OS (Ocula Sinistra), whereas arRP patients without RP1 mutations (−0.50 D OD; −0.75 D OS) and Usher syndrome patients (−0.50 D OD; −0.38 D OS) were significantly less myopic (p<0.0001). Conversely, myopia of xlRP patients with either an RPGR mutation (−4.50 D OD; −5.25 D OS) or an RP2 mutation (−6.25 D OD; −6.88 D OS) was not significantly different from the arRP group with RP1 mutations. arRP without RP1 mutations, Usher syndrome and adRP with RP1 mutation had a narrow IQR (−9.06 to −1.13 D), whereas arRP with RP1 mutations and xlRP with RP2 or RPGR mutations had a larger range (−9.06; −1.13 D). Conclusions: arRP patients with RP1 mutations have myopia not different from patients with xlRP with RP2 or RPGR mutations, while RP patients from other genetic subgroups were emmetropic or mildly myopic. We suggest that arRP patients with high myopic refractive error should be preferentially analysed for RP1 mutations.